KAJIAN ARSIP BELANDA PADA KASUS-KASUS PEROMPAKAN KAPAL Dl KALIMANTAN - Andi Nuralang (Balai Arkeologi Kalimantan Selatan, 2008)
Piracy in general is illegal act of violence at sea which become fearful subject to everyone including sea voyagers and ship owners in the waters of Kalimantan. Data on such piracies are recorded in Dutch archives. However, based on Indonesian perspective in regard to the so called 'piracy' claimed by the Dutch, a number of scholars suspect that it was a political strategy of Dutch to underline the violent action of the Indonesian who in fact merely tried to reclaim their rightful economic assets. In this article, I use historical approach to explore several Dutch archival data about piracy in the waters of Kalimantan, which is further re-examined by several studies on such piracy. Additionally, I present an archaeological data obtained from the Barito River indicating a spot where the so called 'piracy' had occurred in the second half of the 191h century.